Prime Editing and Base Editing in Human Hematopoietic Stem Cells Toward Scarless Correction of Monogenic Blood Disorders - Atul Khajuria (International Journal of Genetic Modifications and Recombinations, 2026)
Monogenic hematological disorders – such as sickle cell disease (SCD), β-thalassemia, and X-linked chronic granulomatous disease (X-CGD) – affect >400, 000 newborns worldwide each year, with a considerable burden in low-resource settings . Although donor-derived allogeneic hematopoietic stem-cell transplantation (HSCT) is widely regarded as curative, its application is limited due to issues of donor availability and graft-versus-host disease (GVHD) and conditioning-related toxicity. DSB-based conventional CRISPR-Cas9 strategies are limited by inefficient homology-directed repair (HDR) and genotoxicity in quiescent HSCs. Base editing (BE) and prime editing (PE) represent non-DSB-dependent capabilities that enable precise, scarless genomic modulations. Methods: A systematic review was performed based on PRISMA 2020 guidelines over PubMed, Scopus, Embase, and ClinicalTrials.gov (January 2020–March 2026). The inclusion criteria covered only primary studies where ≥15% editing efficiency was achieved in human or murine CD34+ HSPCs along with functional validation. A total of 98 studies were included in the review. Data were combined using random-effects meta-analysis, and the quality of evidence was graded according to GRADE methodology . Findings: Base editing led to 40–90% correction efficiencies in HSPCs, while prime editing was efficient (15–60%) but active over a larger range. Early-phase clinical trials (n≈150) showed 3–5 g/dL increases in hemoglobin and transfusion independence in 60–75% of subjects, with positive safety profiles and no evidence of clonal hematopoiesis. in vivo delivery strategies achieved 10–30% editing comprehensiveness. Interpretation: Conventional CRISPR-Cas9 systems have reduced efficiency, and base and prime editing are more accurate and safer. Developments in the delivery systems and scalability will be pivotal to making this approach widely adopted clinically. Regulatory harmonization and equitable access frameworks are still crucial for global impact.
Keywords: Base editing; CRISPR-Cas9 gene editing; Hematopoietic stem and progenitor cells (HSPCs); Monogenic hematological disorders; Prime editing